2014
DOI: 10.2139/ssrn.2531634
|View full text |Cite
|
Sign up to set email alerts
|

Smart or Selfish - When Smart Guys Finish Nice

Abstract: In three different variants of an one-shot public good game I analyze the relationship between cooperation and cognitive abilities, assessed through the cognitive reflection test (CRT). In a between-subjects design, the baseline case is contrasted with two treatment conditions that allow to control for two potentially moderating factors: By employing a test for the presence of confusion, the first condition scrutinizes whether higher cognitive abilities are correlated with cooperation proper or simply grant a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
(42 reference statements)
2
20
0
Order By: Relevance
“…On the one hand our rejection of the FII hypothesis is in line with a number of recent papers (Fiedler et al, 2013;Tinghög et al, 2013;Martinsson et al, 2014;Duffy and Smith, 2014;Verkoeijen and Bouwmeester, 2014;Achtziger et al, 2015;Kocher et al, 2016;Lohse, 2016;Capraro and Cococcioni, 2016;Tinghög et al, 2016) and a large scale replication project (Bouwmeester et al, 2017) which also suggest that in some instances behaving fairly might not be intuitive and might even require additional deliberation or stronger self-control. On the other hand, our results are surprising at least to the degree that they contradict a significant number of previous studies which tend to find that time pressure or other forms of inducing intuitive decision making lead to more cooperative or fair choices.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the one hand our rejection of the FII hypothesis is in line with a number of recent papers (Fiedler et al, 2013;Tinghög et al, 2013;Martinsson et al, 2014;Duffy and Smith, 2014;Verkoeijen and Bouwmeester, 2014;Achtziger et al, 2015;Kocher et al, 2016;Lohse, 2016;Capraro and Cococcioni, 2016;Tinghög et al, 2016) and a large scale replication project (Bouwmeester et al, 2017) which also suggest that in some instances behaving fairly might not be intuitive and might even require additional deliberation or stronger self-control. On the other hand, our results are surprising at least to the degree that they contradict a significant number of previous studies which tend to find that time pressure or other forms of inducing intuitive decision making lead to more cooperative or fair choices.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
“…Furthermore, Tinghög et al (2016) find that time pressure does not affect the fraction of fair choices in (modified) dictator games. Finally, findings in Capraro and Cococcioni (2016) and Lohse (2016) suggest that placing subjects under stronger time pressure leads to more selfish choices in public good games. Similarly, Mrkva (2017) finds that time pressure leads to an increase of selfish choices in modified dictator games with high stakes.…”
Section: Introductionmentioning
confidence: 95%
“…According to Kohlberg’s rationalism 29 30 31 32 , abstract ethical principles are applied only at the third, post-conventional , level of reasoning, requiring a high amount of cognitive resources. In line with this view, a recent experiment has shown that time pressure decreases cooperation among subjects with high cognitive abilities 34 .…”
mentioning
confidence: 77%
“…Verkoeijen & Bouwmeester (2014), Strømland, Tjotta and Torsvik (2016) and Lohse (2016) all found no overall effect of time pressure on cooperation; if anything, Lohse (2016) found that time pressure decreases cooperation, but only among subjects who score high in the CRT. Rand et al (2012).…”
Section: Review Of the Empirical Evidencementioning
confidence: 98%